IMPLEMENTASI PENGADAAN BARANG DAN JASA ALAT TULIS KANTOR PADA BAGIAN UMUM SETDA KABUPATEN MERAUKE - Coleta Maskikit (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2021)
Procurement of goods/services for Office Stationery is a supporting factor in supporting administrative functions in both government and private offices related to administration. Procurement of Office Stationery in a planned and organized manner can have a good impact on each unit or workspace in providing services to the community, of course, really need office stationery so that work activities can run as expected. The process of procuring goods/services is regulated in Presidential Regulation number 16 of 2018, Article 6 concerning the principles in the procurement of goods/services as follows: efficient, effective, transparent, open, fair, non-discriminatory, and accountable. The system of using the state budget in the procurement of goods/services is something that the government must pay attention to, through the Supreme Audit Agency, which has the right to impose sanctions in the event of misuse of the state budget. In carrying out the process of procuring goods/services in the form of office stationery, it is necessary to have a policy in making decisions from a head of the General Section so that there is no delay in the procurement of goods/services.